1998
DOI: 10.1101/gad.12.8.1155
|View full text |Cite
|
Sign up to set email alerts
|

DWnt-2, a Drosophila Wnt gene required for the development of the male reproductive tract, specifies a sexually dimorphic cell fate

Abstract: The sexually dimorphic characteristics of the reproductive tract in Drosophila require that cells of the gonad and the genital disc be assigned sex-specific fates. We report here that DWnt-2, a secreted glycoprotein related to wingless, is a signal required for cell fate determination and morphogenesis in the developing male reproductive tract. Testes from DWnt-2 null mutant flies lack the male-specific pigment cells of the reproductive tract sheath and the muscle precursors of the sheath fail to migrate norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 36 publications
8
105
0
Order By: Relevance
“…Wnt molecules play an important role in sexual determination and differentiation in species ranging from Drosophila to mice (30,31). Our results also showed that Wnt signaling is important for proper sexual differentiation in human males.…”
Section: Discussionsupporting
confidence: 60%
“…Wnt molecules play an important role in sexual determination and differentiation in species ranging from Drosophila to mice (30,31). Our results also showed that Wnt signaling is important for proper sexual differentiation in human males.…”
Section: Discussionsupporting
confidence: 60%
“…Of the Drosophila Wnts, only DWnt2 is expressed in the posterior gut primordium at the appropriate time. However, £ies homozygous for a null allele of DWnt2 are viable (Kozopas et al 1998), suggesting either that Dwnt2 is not active in specifying tubule cells or that a maternal contribution of Dwnt2 provides the ligand. Further work is required to assess the role of Dwnt2 and if necessary, to search for other members of the Wnt family, as the full sequence of the £y genome becomes available.…”
Section: The Allocation Of Malpighian Tubule Cells and The Formation mentioning
confidence: 99%
“…In Drosophila, disruption of Dwnt-2 gene causes loss of the male-specific pigment cells in the reproductive tract sheath (37), indicating that Wnt signaling carries crucial functions in testicular development. During mouse spermiogenesis, the round spermatids proceed to an elongation phase in which they are sculptured into the shape of mature spermatozoa (38).…”
Section: Role Of Nkd1 In Mouse Embryonicmentioning
confidence: 99%